Experimental, quantum computational study and in vitro antidiabetic activity of oxidovanadium(IV) complexes incorporating 2, 2'-bis(pyridylmethyl)amine and polypyridyl ligands. Issue 7 (2nd April 2020) - Patel, Neetu; Prajapati, A. K.; Jadeja, R. N.; Tripathi, I. P.; Dwivedi, N.
Abstract: This article describes synthesis and characterization of three oxidovanadium(IV) complexes using BPA (BPA = 2, 2'-bis(pyridylmethyl)amine), 2, 2-bipyridyl and 1, 10-phenanthroline. These complexes were characterized by elemental analysis, spectroscopic (UV-vis, IR and EPR) and electrochemical methods. Room temperature magnetic susceptibility data show the paramagnetic nature of the complexes. Complexes were also characterized by electron paramagnetic resonance (EPR) spectral techniques. The optimized molecular structures show the presence of N3 O3 /N5 O donor atoms in six-coordinate geometry. These complexes were evaluated and compared using thermogravimetric analysis and powder X-ray diffraction techniques. The species exhibit only one-electron reduction wave at a more negative potential. The catalytic activity of these complexes was also explored to mimic α-glucosidase and α-amylase activity. Moderate α-glucosidase and α-amylase inhibitors are shown by all complexes. These observations are expected to expand the possibility of designing new oxidovanadium(IV) complexes with significant anti-diabetic properties. Graphical Abstract: